2022
DOI: 10.5194/sd-30-43-2022
|View full text |Cite
|
Sign up to set email alerts
|

COSC-2 – drilling the basal décollement and underlying margin of palaeocontinent Baltica in the Paleozoic Caledonide Orogen of Scandinavia

Abstract: Abstract. The Collisional Orogeny in the Scandinavian Caledonides (COSC) scientific drilling project aims to characterise the structure and orogenic processes involved in a major collisional mountain belt by multidisciplinary geoscientific research. Located in western central Sweden, the project has drilled two fully cored deep boreholes into the bedrock of the deeply eroded Early Paleozoic Caledonide Orogen. COSC-1 (2014) drilled a subduction-related allochthon and the associated thrust zone. COSC-2 (2020, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…1). However, the effect of the lithology on the biomass was not feasible to predict prior to field sampling as the expected lithology from the siting differed from the drilled lithology (Lorenz et al, 2022).…”
Section: Rock Core Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…1). However, the effect of the lithology on the biomass was not feasible to predict prior to field sampling as the expected lithology from the siting differed from the drilled lithology (Lorenz et al, 2022).…”
Section: Rock Core Samplesmentioning
confidence: 99%
“…The sampling procedure and contamination control were described in detail in Lorenz et al (2022). Briefly, rock core samples with core recovery to characterize potential contaminants introduced during the drilling operation.…”
Section: Field Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, seismic reflection imaging across the central Scandinavian Caledonides shows a pervasively reflective upper crust, down to at least 15 km present depth, characterized by sub‐horizontal and west‐dipping reflectors (Hurich et al, 1989; Juhlin et al, 2016; Juhojuntti et al, 2001; Palm et al, 1991). These reflectors are intriguing because they occur under the shale décollement and deep drilling indicated that they are likely to originate from mafic intrusions (Lorenz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Collisional Orogeny in the Scandinavian Caledonides, a scientific drilling project conducted in 2020, located in central Sweden [51].…”
Section: Syntrophymentioning
confidence: 99%